RURAL HOUSEHOLD IN THE PROCESS OF MODERNIZATION-DEVELOPMENT OF THE ROMANIAN RURAL AREA - Lorena CHIȚEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The goal of this paper was to establish a causal relationship between the socio-economic modernization level and the development level of the Romanian rural area, as main point of modernization of the rural household. The starting point in establishing this causal relationship was the development of a theoretical model for the assessment of the modernization and socio-economic development level of the rural area in terms of rural household modernization potential. The output of these models was 3 composite indices that were analysed both as independent indices, in dynamics, and in relation to the other indices, as well as to the dimensions and indicators related to each index. The main hypothesis of the research was the existence of an intrinsic link between the modernization degree and the socio-economic development of the rural area, thus the integration of modernization elements entailing development and implicitly, at rural household level, the continuous improvement of the quality of life and welfare of the rural population. The rural household was considered an important component of the Romanian rural space, being the driving engine that makes all the subsystems of the rural space work.